Liquid dish wash solution – can it be an alternative in future for the expensive and hazardous xylene in hematoxylin and eosin staining of paraffin sections - Dr. Swaroop Raj B.V.; Dr Divya C; Dr. Harendra Kumar ML (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Xylene is the most commonly used clearing agent as it has excellent deparaffinising and clearing properties. Commercial xylene is a clear, colourless liquid that has a sweet and aromatic odour. However, xylene is not only expensive but also has detrimental effect on human health such as hepatitis, chemical pneumonitis, depression, anaemia, etc. Hence in this study we are replacing xylene with commercially available liquid dish wash solution (LDW) which is not only cheap but also non biohazardous. Aims: To assess the efficacy of LDW with xylene as a deparaffinising and clearing agent in routine hematoxylin and eosin staining (H&E). Materials and Methods: Blocks from 20 consecutively submitted samples at RL Jalappa Hospital between Jan – June 2015 each of breast, Cervix, Lymphnode, Fat, Salivary Gland, Muscle and Alimentary Tract was taken and two sections of 4-micron thickness were cut and deparaffinised using Liquid Dish Wash and Xylene respectively followed by H & E Staining. The 280 sections of the 140 blocks were evaluated and scored by two pathologists independently for nuclear staining, cytoplasmic staining, uniformity, clarity and crispness. Results: In the samples evaluated LDW seems to be on par with xylene cleared sections in terms of nuclear and cytoplasmic detail, clarity and crispness. However Xylene cleared sections showed slightly better uniform staining. However both sections were equally good for reporting. Conclusion: Liquid dish wash solution is an excellent alternative to xylene in H&E Staining. However more extensive studies need to be done on other types of tissues for validation